Respuesta :
So firstly, factor out h on the left side: [tex] h(b+r)=25 [/tex]
Next, divide both sides by h: [tex] b+r=\frac{25}{h} [/tex]
Lastly, subtract both sides by b and your answer will be [tex] r=\frac{25}{h}-b [/tex]
Answer:
[tex]r=\frac{25}{h}-b[/tex] will be the answer.
Step-by-step explanation:
the given equation is bh + hr = 25
We have to solve this equation for the value of r.
We divide this equation by bh first.
[tex]\frac{bh+hr}{bh}=\frac{25}{bh}[/tex]
1 + [tex]\frac{hr}{bh}=\frac{25}{bh}[/tex]
[tex]1 + \frac{r}{b}=\frac{25}{bh}[/tex]
[tex]\frac{r}{b}=\frac{25}{bh}-1[/tex]
[tex]r=b(\frac{25}{bh}-1)[/tex]
[tex]r=\frac{25}{h}-b[/tex]
Therefore, [tex]r=\frac{25}{h}-b[/tex] will be the answer.